Daily or weekly rotational feeding of Bovatec®- and Rumensin®/Tylan® to cattle on a steam-flaked corn finishing ration - Robert T. Brandt Jr. (Kansas Agricultural Experiment Station Research Reports, 1988)
One hundred sixty-five crossbred steers averaging 823 lb were utilized to evaluate the daily or weekly rotational feeding of ionophores. Treatments were (g/ton of feed, 90% dry basis): 1) Bovatec (B; 30), 2) Rumensin plus Tylan (RT; 25 and 10, respectively), 3) treatments one and two in a daily rotation (D), and 4) treatments one and two in a weekly rotation (W). Steers fed RT consumed less (Por W steers. No differences (P>.15) in daily gain were observed, suggesting that the increased consumption by B, D) and W steers was accompanied by an al teration in passage rate and/or other kinetics of digestion, such that additional consumption was poorly utilized. Thus, RT steers gained 3.9% more efficiently (P=.06) than B steers and numerically more efficiently than D or W steers. No differences were observed among treatments for carcass quality or yield. Performance of D and W steers did not differ from that predicted by the performance of steers fed B and RT fed separately, indicating no synergism from alternate feeding of ionophores in this study.
Keywords: Kansas Agricultural Experiment Station contribution; no. 88-363-S; Cattlemen& #x27; s Day; 1988; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 539; Beef; Bovatec®; Rumensin®/Tylan®; steam-flaked corn; Rotational feeding